Indicators of extreme hydroclimatic events in the Ouémé watershed at Bonou's outlet in West Africa - (:unkn) unknown (My University, 2018)
This research aims to characterize the indicators relating to extreme hydroclimatic events in Ouémé Watershed at Bonou’s outlet. To achieve this objective, climatological data (daily rain, daily temperatures, potential daily evapotranspiration), hydrometric data (daily flows), reanalysis data (atmospheric pressure, relative humidity, wind speed, West African Monsoon Indices), the ocean surface temperature on the Cotonou coast and land use mapping data of 1986, 2000, 2015 are used. The analysis of the hydroclimatic variability revealed that during the 1951-2015 period, the study area is marked by two breaks stationarity (1968 and 1987) which divided the series into three sub-periods. The rainfall variability reveals a regression of 18 % (in the south), 16 % (in the center) and 15.8 % (in the north) between the first sub-period (1951-1968) and the second sub-period (1969-1987), while the last sub-period (1988-2015) is marked by a rainfall recovery of 15 % (in the south), 16.3 % (in the center) and 15.7 % (in north) relative to the previous sub-period (1969-1987). This is not without consequences on the hydrological dynamics of the study area. In this sense, it is noted that there is a regression of 49.27% of the average annual flows between the 1951-1968 and 1969-1987 sub-periods and a 65 % increase between the 1969-1987 and the 1969-1987 sub-periods. 1988-2015. In the last sub-period (1988-2015), the results also reveal an increase in the indicators of extreme hydroclimatic events likely to cause floods Ouémé Watershed at Bonou’s outlet. The results shows that daily maximum rainfall has an occurrence of 2 years, 5 years, 10 years for strong rainfall events; 20 years, for very heavy rain events, 50 years and over for extremely heavy rain events in the study area. The maximum flow rates in 24 hours at the sametime as the return periods. The maximum flow rates of 50th quantiles occur every two years (02 years), the maximum flows corresponding to th
Keywords: African Research